Morphotectonic and morphostructural investigation in northwestern Minas Gerais State, Brazil: a lineament mapping assessment - Bragança, Mário Teixeira Rodrigues; Barros, Luiz Fernando de Paula; Oliveira, Déborah de (Revista Brasileira de Geomorfologia, 2023)
This study aimed to investigate whether linear natural features are associated with structural or tectonic control of landforms and current drainage patterns in northwestern Minas Gerais State (Southeastern Brazil). To answer this question, more than 1,700 lineaments were manually mapped in a broader area encompassing the Paracatu and Urucuia River catchments. One satellite image scene (Operational Land Imager/Landsat-8), three different digital elevation models (Shuttle Radar Topography Mission, Advanced Spaceborne Thermal Emission and Reflection Radiometer-Global digital elevation model, and Advanced Land Observing Satellite-Phased Array L-band Synthetic Aperture Radar), and digitised analogical maps (geologic and topographic maps) were used to draw linear geometric features representing the lineament population. The resulting vector databases were integrated in a Geographic Information System for quantitative and spatial analyses, which resulted in two main trending lineament sets: NNW-SSE and NE-SW. Subsequent field assessments revealed that numerous lineaments from the first set were correlated to the formerly Upper Precambrian reverse and strike-slip faults. The second set were correlated to NE-SW normal faults derived from the Mesozoic-Cenozoic tectonic event following the breakup of Gondwana. These datasets contribute to a better understanding of the regional-, sub-regional-, and catchment-scale features underlying the structural control of the drainage network arrangement and pattern, which present long straight channels and are interrupted by anomalous and prominent bends that strictly fit major structural directions.